PENGARUH RASIO KESEHATAN BANK DENGAN RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL (RGEC) TERHADAP PROFITABILITAS BANK - Nurasih Yuni Utami, 12.05.52.0122; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2016)
This study aims to transform and analyze the influence of risk profile, good corporate governance, earnings, and capital on profitability in banking companies listed in Indonesia Stock Exchange 2011-2014 period. In this study, researchers used data population banking financial companies listed on the Stock Exchange during 2011-2014. The method used is purposive sampling method. Test equipment in this study using multiple linear regression, partial test (t test) and a simultaneous test of f (f test). The results of this study are credit risk, and corporate governance (CG) a negative effect on profitability. Earning a positive effect on profitability. Meanwhile, liquidity risk and capital does not affect the profitability.Keywords: Risk Profile, Good Corporate Governance, Earning, Capital, Profitabilitas